Reliability of scores obtained through protected areas manager’s self-assessments using the Management Effectiveness Tracking Tool (METT) : a case study of South Africa’s protected areas - Mabaso, Andrias Mzokhona (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.